Klaim Asuransi Pesawat Udara Sewa Guna Usaha (Operating Lease) Sebagai Objek Jaminan Fidusia - Sukarmi, Sukarmi; Sudirman, M.; Egawati, Dwi (UI Scholars Hub, 2020)
Airlines in the process of procurement of an Aircraft, one of which is through Operating Lease with the Leasing Company. The Leasing Company (Lessor) in purchasing an Aircraft with funding mechanism from the Bank shall encumber the Aircraft with a mortgage as its securities. In the Aircraft Lease Agreement, Insurance Claim over the Aircraft shall also be encumbered with fiduciary by Airlines. Nevertheless, under Article 10 paragraph b Law of The Republic of Indonesia Number 42 of 1999 on Fiduciary (hereinafter referred to as UUJF) states that unless otherwise agreed, Fiduciary includes the Insurance Claims in the event that the Aircraft which is the object of Fiduciary has insured.